2012
DOI: 10.1002/nau.22264
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin therapy improves recovery of the neuromuscular continence mechanism following simulated birth injury in rats

Abstract: Aims Stress Urinary Incontinence (SUI) affects women both acutely and chronically after vaginal delivery. Current SUI treatments assume the neuromuscular continence mechanism, comprised of the pudendal nerve (PN) and external urethral sphincter (EUS), is either intact or irreparable. This study investigated the ability of neurotrophin therapy to facilitate recovery of the neuromuscular continence mechanism. Methods Virgin, Sprague Dawley rats received simulated childbirth injury or sham injury and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Generally, BDNF downregulation after muscle injury enables neuromuscular junction repair (46), but in childbirth injury is associated with delayed pudendal nerve regeneration after VD and PNC, both functionally and anatomically (27,40). Exogenous BDNF has been shown to improve urinary continence and EUS recovery after simulated birth injury (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, BDNF downregulation after muscle injury enables neuromuscular junction repair (46), but in childbirth injury is associated with delayed pudendal nerve regeneration after VD and PNC, both functionally and anatomically (27,40). Exogenous BDNF has been shown to improve urinary continence and EUS recovery after simulated birth injury (17).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF upregulation likely promotes axonal regrowth since ␤ II -tubulin, which constitutes microtubules for neurofilaments for axon, when upregulated, indicates the regenerative effort of the neuron in response to injury (34). Moreover, expression of ␤ II -tubulin, as measured by mRNA levels, has been used to assess neurotrophin treatments (6,17,52). Therefore, ␤ IItubulin upregulation is evidence of pudendal nerve regeneration, whereas BDNF upregulation suggests it is promoted by the electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Takahashi et al reported on the efficacy of local b-FGF injections into damaged RS in female rats. 18 Gelatin hydrogels were used for sustained release of b-FGF.…”
Section: Urethral Sphinctermentioning
confidence: 99%
“…Gill et al reported that continuous neurotrophin treatment using brain-derived neurotrophic factor accelerated continence recovery after simulated childbirth injury, stimulating neuroregeneration, and facilitating RS recovery and reinnervation. 19 Therefore, cytokine regulation might also be useful as a novel therapeutic modality for the treatment of urinary incontinence.…”
Section: Urethral Sphinctermentioning
confidence: 99%